1970
DOI: 10.1104/pp.46.6.768
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Regulation of Phytochrome-mediated Processes in Bean Roots by the Neurohumor, Acetylcholine

Abstract: Using pharmacological and chromatographic techniques, it was shown that acetylcholine was present in all organs of both light-and dark-grown mung bean seedings (Phaseolus aureus). The Acetylcholine, given for 4 minutes in the dark, was able to substitute for red light in reducing the formation of secondary roots, inducing increased H+ efflux, and causing the root tips to adhere to a negatively charged glass surface. Acetylcholine-esterase and atropine inhibited the latter phenomenon, whereas eserine inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
89
0
1

Year Published

1972
1972
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(94 citation statements)
references
References 23 publications
4
89
0
1
Order By: Relevance
“…It is interesting to note that, whenever ChE activity was detected in plants, eserine was much less effective in vitro compared to animal ChE (27,28). On the other hand, when applied in vivo, eserine was active in relatively low concentrations even in plant tissues (8,13,16). This discrepancy might be explained by the possibility that eserine is being ionized in vivo and this corresponds to the increased activity observed in vivo.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…It is interesting to note that, whenever ChE activity was detected in plants, eserine was much less effective in vitro compared to animal ChE (27,28). On the other hand, when applied in vivo, eserine was active in relatively low concentrations even in plant tissues (8,13,16). This discrepancy might be explained by the possibility that eserine is being ionized in vivo and this corresponds to the increased activity observed in vivo.…”
Section: Discussionmentioning
confidence: 61%
“…The molecular weight of the cholinesterase was estimated to be greater than 200,000, but at least one smaller form was observed. It is suggested that the large form of cholinesterase is converted to the smaller form by proteolysis.Acetylcholine has been shown to participate in phytochrome-mediated processes in bean roots (16), and the results obtained in the above work suggested that bean roots might contain a cholinesterase which functions to regulate the content of ACh' in roots. Other workers (8, 9, 13) have also reported that whenever ACh was found to play a role in physiological processes in plant tissues, ChE inhibitors increased the effects of ACh or were essential for getting any effects of ACh.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Our main finding is that, ACh prolongs the repolarization phase of the AP and Cd 2+ at 20 μM has no effect on the AP by itself, but increases the effect of ACh. Existing experimental data shows that the primary mechanism of action of ACh in plant cells could be via the regulation of membrane permeability to protons [21], potassium ions [22], chloride ions [23] and Ca 2+ [24]. On the other hand, there is experimental evidence that the same transport systems are involved in generation of action potential in plant cells [6,8,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme also has other properties in common with acetylcholinesterase (EC 3.1.1.7), including inhibition by relatively low concentrations, roughly 1 ,uM, of neostigmine and organophosphates such as paraoxon and inhibition by excess substrate (>1 mM) (12). Furthermore, acetylcholine itself has been identified in extracts of Phaseolus aureus (7). Riov and Jaffe (12) concluded that the enzyme from Phaseolus autreus is a cholinesterase, and subsequently a number of reports (4,11,13) (2,4,6), and are present in species in the Leguminosae and Solanaceae (3,5,8,15).…”
mentioning
confidence: 99%